Creep behavior in a γ′ strengthened Co–Al–W–Ta–Ti single-crystal alloy at 1000 °C. (1st March 2015) - Xue, F.; Zhou, H.J.; Shi, Q.Y.; Chen, X.H.; Chang, H.; Wang, M.L.; Feng, Q.
Abstract : The tensile creep behavior and microstructural stability of a Co–Al–W–Ta–Ti single-crystal alloy were investigated at 1000 °C. Long-term aging at 1000 °C for 1000 h revealed stable γ–γ′ structure with 75% γ′ volume fraction. The measured positive lattice misfit resulted in directional coarsening parallel to the applied stress during creep. The γ–γ′ interfacial dislocation networks and shearing of γ′ precipitates with stacking faults and antiphase boundaries appeared to contribute to the creep resistance with 1.0% creep stain.